Effects of Cold Plasma and Ozone Water Treatment on Micronutrient Solubility - Dharti Thakulla; Paul R. Fisher (Horticulturae, 2023)
Cold plasma and ozone sanitation of irrigation solutions can oxidize both microbes and non-target micronutrients because their high oxidation-reduction potential (ORP) is a non-selective mode of action. The objective of this study was to evaluate the effects of cold plasma and ozone treatment on oxidation of iron and manganese in nutrient solutions containing one of four iron chelates (iron-ethylenediaminetetraacetic acid (Fe-EDTA), iron-diethylenetriaminepentaacetic acid (Fe-DTPA), iron-ethylenediamine-N,N′-bis(2-hydroxyphenylacetic acid) (Fe-EDDHA), and hydroxybenzyl ethylenediamine (Fe-HBED)). Nutrient solutions were recirculated through the cold plasma or ozone system until the ORP reached 700 mV. The concentrations of total dissolved iron, manganese, and chelated iron were measured before and after passing through the treatment systems. Both cold plasma and ozone oxidized chelates and decreased the solubility of iron and manganese. Cold plasma and ozone had similar effects on micronutrients, pH, electrical conductivity, and dissolved oxygen at a standardized target ORP of 700 mV. Fe-EDTA was the most resistant chelate to oxidation. With Fe-EDTA, ORP increased more quickly, and the concentration of chelated Fe decreased less with the increasing ORP over time compared with Fe-DTPA, Fe-EDDHA, and Fe-HBED. The concentration of chelated Fe decreased by up to 80% for EDDHA at 700 mV compared with a 20% decrease for EDTA. The concentration of Mn decreased by up to 85% at 700 mV. The design of water treatment with cold plasma or ozone therefore requires consideration of secondary effects on micronutrients. The treatment dosage, flow rate, and nutrient solution at a particular grower operation are likely to affect the quantity of micronutrient fertilizer that needs to be supplemented following treatment. Use of Fe-EDTA is one strategy to reduce the loss of iron and increase residual ORP that is available for sanitation.